Effects of α1/α2 ratios and drying temperatures on the properties of gelatin films prepared from tilapia (Tilapia zillii) skins. (January 2016) - Chen, Shulin; Tang, Lanlan; Hao, Gengxin; Weng, Wuyin; Osako, Kazufumi; Tanaka, Munehiko
Abstract: Effects of α1 /α2 ratios and drying temperatures on the properties of tilapia skin gelatin films were investigated. Tensile strength (TS) of α1 -subunit based films and α2 -subunit based films were 30.4 MPa and 12.8 MPa, respectively. When films were prepared from α-subunits at α1 /α2 ratio of 2/1, both TS and elongation at break (EAB) of films were the highest. The color of α-subunit based composite films was similar to that of α2 -subunit based films. However, no obvious changes in the SDS-PAGE patterns were observed between film-forming solutions and films. On the other hand, the TS and EAB of α-subunit based composite films prepared at 10 °C or 15 °C were much higher than those of films prepared at 20 °C or 25 °C. Circular dichroism analysis revealed that triple helical structure was formed in the films containing α1 -subunit dried at 15 °C or below, thus forming strong strength films. Graphical abstract: Highlights: Strength of α1 -subunit based films was higher than that of α2 -subunit based films. The highest TS of films was prepared from α-subunits at α1 /α2 ratio of 2. The α1 -subunit plays an important role in the α-subunit based film formation. Triple helical structure was formed in films below denaturation temperature.